Sequence Effect in Parkinson’s Disease Is Related to Motor Energetic Cost - Tinaz, Sule; Pillai, Ajay S.; Hallett, Mark (Frontiers in Neurology, 2016)
Bradykinesia is the most disabling motor symptom of Parkinson’s disease (PD). The sequence effect, a feature of bradykinesia, refers to the rapid decrement in amplitude and speed of repetitive movements (e.g., gait, handwriting) and is a major cause of morbidity in PD. Previous research has revealed mixed results regarding the role of dopaminergic treatment in the sequence effect. However, external cueing has been shown to improve it. In this study, we aimed to characterize the sequence effect systematically and relate this phenomenon to the energetic cost of movement within the context of cost-benefit framework of motor control. We used a dynamic isometric motor task with auditory pacing to assess the sequence effect in motor output during a 15 s task segment in PD patients and matched controls. All participants performed the task with both hands, and without and with visual feedback. Patients were also tested in “on”- and “off”-dopaminergic states. Patients in the “off” state did not show higher sequence effect compared to controls, partly due to large variance in their performance. However, patients in the “on” state and in the absence of visual feedback, showed significantly higher sequence effect compared to controls. Patients expended higher total motor energy compared to controls in all conditions and regardless of their medication status. In this experimental situation, the sequence effect in PD is associated with the cumulative energetic cost of movement. Dopaminergic treatment, critical for internal triggering of movement, fails to maintain the motor vigor across responses. The high motor cost may be related to failure to incorporate limbic/motivational cues into the motor plan. Visual feedback may facilitate performance by shifting the driving of movement from internal to external, or, alternatively, by functioning as a motivational cue.